Finite and Boundary Element Tearing and Interconnecting Solvers for Multiscale Problems - Pechstein, Clemens; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Tearing and interconnecting methods, such as FETI, FETI-DP, BETI, etc., are among the most successful domain decomposition solvers for partial differential equations. The purpose of this book is to give a detailed and self-contained presentation of these methods, including the corresponding algorithms as well as a rigorous convergence theory. In particular, two issues are addressed that have not been covered in any monograph yet: the coupling of finite and boundary elements within the tearing and interconnecting framework including exterior problems, and the case of highly varying (multiscale) coefficients not resolved by the subdomain partitioning. In this context, the book offers a detailed view to an active and up-to-date area of research.
Preliminaries -- One-level FETI/BETI Methods -- Multiscale Problems -- Unbounded Domains -- Dual-Primal Methods -- References -- Index -- List of Symbols.
Keywords: Mathematics; Computer science; Numerical analysis; Mathematics; Numerical Analysis; Computational Science and Engineering